The impact of economic crises on youth unemployment in rural areas of the European Union - Kiryluk-Dryjska, Ewa; Baer-Nawrocka, Agnieszka (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The objective of this study was to research the vulnerability of youth unemployment in rural areas of the European Union to the global financial crisis of 2007 and COVID-19 pandemic. Methodology: The Eurostat data were used to show the differences in unemployment rates of young people in rural areas before and after the financial crisis of 2007 and the COVID-19 pandemic. The results were compared with the data for older people as well as young people living elsewhere using Eurostat database age groups. Results: The results demonstrate that young people in rural areas are more severely affected by the crises compared to other analysed groups. However, the pace of recovery from high unemployment in this group is higher compared to urban areas. The authors also found that in EU countries where unemployment rates increased significantly after the 2007 financial crisis, young people in rural areas continue to face high unemployment rates above the EU average. Implications and recommendations: In order to design rural development programmes to support job creation it is of crucial importance to monitor levels of the rural youth labour market. Moreover, active labour policies, such as training and education, should be undertaken with the objective of increasing flexibility of young people in the rural labour market. Originality/value: The novelty of this research lies in its empirical demonstration that youth unemployment in rural areas is particularly vulnerable. Therefore, it warrants special attention in policy-making.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 84-96
Keywords: rural areas; youth unemployment rate; economic crises